PENGEMBANGAN MULTIMEDIA INTERAKTIF ARTIKA PADA MATA PELAJARAN INFORMATIKA KELAS VII SMP - Ardhani, Aulya; Bentri, Alwen; Novrianti; Maiziani, Fitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the development process of ARTIKA (Articulate Storyline and Informatics), an interactive multimedia product for seventh-grade Informatics, and to determine its validity and practicality. This study was motivated by the limited instructional media used in Informatics classes at MTsN 11 Agam, largely because the subject teacher lacks a technology-related educational background, so that classroom materials tend to be simple, non-interactive slides; daily assessment data further show that seventh-grade students' average scores of 68.86 still fall below the 75-point mastery criterion, while the school's computer laboratory provides only eight functioning units for six classes. A Research and Development approach following the 4D model (Define, Design, Develop, Disseminate) proposed by Thiagarajan was applied. The product was built with Articulate Storyline, supported by Canva for visual assets and a web-to-APK converter so that it can run on computers and smartphones, offline and online. Content covers six Informatics topics for two semesters under the Merdeka Curriculum, packaged with adventure-themed illustration, narrative text, interactive navigation buttons, and background audio. Feasibility was examined through expert judgment involving one material expert and two media experts, followed by a limited field trial with thirty students of class VII A. Results show a material validity score of 5.00, media validity scores of 4.77 and 4.93, and a practicality score of 4.69, all falling in the very valid and very practical categories. These findings suggest ARTIKA can serve as a flexible and engaging alternative medium that helps overcome facility constraints in Informatics instruction.